Expenditure Pattern of College Girls in Dindigul Town, Tamil Nadu - An Exclusive Study - Rajasekar, N.; Manimaran, S.; Kokila, M. S. (Indian Journal of Marketing, 2008)
In an increasing and competitive world of raising purchasing power, compulsion of dual income in families becomes important. Thereby in most of the families in India, both the spouses go to work place in order to uplift their family and to have a smooth running of a family. As a result, very less time is devoted to take care of their children. Most of the families in India are nuclear, since both the spouse are busy with their work; children take care of themselves by fulfilling their wants. Due to the lack of time, parents make the habit of giving pocket money to children to meet their expenses without depending on them. Children in such type of families have been given freedom of choice in purchasing; there is a chance of misusing the money. The study covers this aspect also.